Legal Compliance Of Taxpayers In Medan Against Voluntary Disclosure Program - Jenny Jenny; Rilawadi Sahputra; Syariful Azmi (International Asia Of Law and Money Laundering, 2023)
This voluntary disclosure Program aims to improve taxpayer compliance by voluntarily disclosing tax-related information. This Program provides an opportunity for taxpayers to avoid sanctions and fines and obtain legal certainty. However, the success of this program is influenced by the understanding of taxpayers, supervision, law enforcement, and quality of service of tax authorities. To improve compliance, there needs to be more effective socialization, stricter law enforcement, better service, and periodic program evaluation. It requires intensive and coordinated efforts from the government, law enforcement officials, and the public to achieve higher levels of compliance and increase state revenue from the tax sector.